Tourists’ Behavioural Pattern in the Consumption of Region-Specific Tangible and Intangible Cultural Heritage Resources in Nigeria - Chigozie Ugochukwu Okoro; Polycarp A. Igbojekwe; Dr. Nsisuk Harrison Akpanabia; Dr. Emmanuel Ukabuilu (Research Parks Publishers, 2021)
This study focused on tourists’ behavioural pattern in the consumption of region-specific tangible and intangible cultural heritage resources in Nigeria. It addresses the extent to which demand for and the production of heritage tourism in Nigeria can be identified by categorization of cultural heritage consumers. The major objective is to define tourist’s behavioural consumption pattern of region-specific cultural heritage resources in terms of identified consumer category or market segment. Data set for the study was gathered through questionnaires structured on 5-point likert scale and yes or no response option. 4,750 respondents were analyzed using the simple descriptive analysis. factors found to influence consumption of cultural heritage resource in relation to other purchase during the event in order of importance include income; Religion; Culture/Cultural Practice; distance from urban center; Gender; Patriotism and Age.